Clinicoepidemiological Study of Cutaneous Leishmaniasis: A Hospital Based Study - Sushmita Pradhan; Shristee Shrestha; Damber Khadka; Niraj Parajuli; Suwash Baral; Daisuke Tsuruta (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Cutaneous leishmaniasis is a tropical disease transmitted by the bite of an intracellular parasite infected sandfly. Visceral leishmaniasis is common in Nepal. However, cutaneous leishmaniasis remains rare with only limited number of cases documented in Nepal.